Erdogans Empire - Cagapty, Soner (New York I.B Tauris, 2020)
"Gradually since 2003, Turkey's autocratic leader Recep Tayyip Erdogan has sought to make Turkey a great power ... Erdogan has picked an unorthodox model in the context of recent Turkish history, attempting to cast his country as a stand-alone Middle Eastern power. In doing so Turkey has broken ranks with its traditional Western allies, including the United States and has embraced an imperial-style foreign policy which has aimed to restore Turkey's Ottoman-era reach into the Arabian Middle East and the Balkans."
Include Index and Bibliography
Keywords: Turkey -- Politics and government -- Presidents -- Middle East